Systematic writing and feedback delivery: upper-intermediate students’ perceptions on benefits and affects - Oportus-Torres, René; Contreras-Soto, Yasmina; Vásquez-Neira, Andrea; Sanhueza-Campos, Cristian; Maluenda-Albornoz, Jorge (Frontiers in Education, 2025)
IntroductionAcademic writing instruction is a complex endeavor which demands adequate practice to consolidate its development. The objective of this study, set in an undergraduate Translation Program across three cohorts, was to explore students’ perceptions regarding the impact of a two-semester intervention aiming to develop academic writing.MethodsAn action research design included weekly tasks and the delivery of written corrective and positive feedback, peer correction and whole-class revision. A total of 137 students answered a questionnaire across three dimensions: (a) linguistic, (b) pedagogical, and (c) affective. Additionally, a focus group examined their perceptions for triangulation.ResultsQuantitative and qualitative analysis indicates that participants value several features, e.g., systematic writing and explicit individual feedback, as these gradually help them consolidate micro (linguistic), macro (organization) and superstructural (theme) skills associated with academic writing. Additionally, a confidence increase and anxiety reduction are reported.DiscussionThese findings are arguably connected with enhanced student self-regulation, self-awareness and self-efficacy triggered by the intervention. This study contributes to the understanding of ecological interventions fostering academic writing development in EFL.